Unlike twins: an NMR comparison of two α-synuclein polymorphs featuring different toxicity. - Julia Gath; Luc Bousset; Birgit Habenstein; Ronald Melki; Anja Böckmann; Beat H Meier (PLoS ONE)
We structurally compare, using solid-state NMR, two different polymorphs of α-synuclein which, as established recently, display contrasting biochemical properties, toxicity, and tropism for cells. We show that both forms, which can each be produced as a pure polymorph, are greatly different in secondary structure. While β-sheets are the dominating secondary structure elements for both polymorphs, they are markedly divergent in terms of number of elements, as well as their distribution. We demonstrate that all identified β-sheets feature an in-register parallel stacking for both polymorphs. The two forms show a different molecular arrangement in the unit cell and distinct dynamic features, while sharing a highly flexible C-terminal domain. The use of reproducible, well-identified conditions for sample preparation and the recording of identical NMR experiments allows for a direct comparison of the results.